3R Activities and Their Effects on Science Learning in Malaysian National Schools - Rahayu, Titik; Setiana, Nurul (Islamic Journal of Integrated Science Education (IJISE), 2024)
This research investigates the impact of Reduce, Reuse, and Recycle (3R) activities on science education in Malaysian national schools. The study uses a qualitative case study approach, collecting data from 45 subjects, including primary school teachers, secondary school teachers, and students. The results show high enthusiasm among teachers and students for implementing the 3Rs in education, despite challenges. The study found that 3R activities are effective in teaching science in a simple and efficient way, encouraging creativity, improving motor development, and encouraging wise use of used goods. The findings suggest that using Reduce, Reuse, and Recycle (3R) activities in science education contributes to environmental education. Future research is recommended to determine the differences and impacts of 3R implementation on science learning, as this research has the potential to significantly impact environmental and sustainability education globally.